INFLUENCE MOTIVATION, ABILITY, AND DISCIPLINE ON PERFORMACE EMPLOYEE DEPARTMENT SALES DAN MARKETING PT PIONIRBETON INDUSTRY JAKARTA - Hartanto, okiy (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The purpose of the research are to: 1) Test empirically influence of working motivation on performance employee, 2) Test empirically influence of working ability on performance employee, 3) Test empirically influence of working discipline on performance employee, 4) Test empirically influence of working motivation, ability, discipline on performance employee. This study used multiple regression analysis. The research was conducted in Sales and Marketing Department of PT Pionirbeton Industry with population of 43 workers, while the data collecting technique used questionnaire and SPSS version 20.0 for data processing. The result show a significant influence of working motivation on performance employee, working ability on performance employee, working discipline on performance employee. Working motivation, working ability, and working discipline on performance employee, The study found that a of the performance employee as dependent variable is influenced by motivation, ability, and discipline. Keywords: working motivation, working ability, working discipline, performance employee.